Reinforcing Post-Disaster Place Identity through Historical Tourism Grounded in the Sense of Place Framework: A Case Study of Gampong Pande - Yumna Alifa; Bagas Dwipantara Putra (TATALOKA, 2026)
Gampong Pande, a historically significant toponym marking the origin of the port city of the Aceh Darussalam Sultanate and the foundation of Banda Aceh city, possesses substantial potential for development as a historical tourism destination. However, in the aftermath of the 2004 Indian Ocean tsunami, a critical paradox has emerged: while physical reconstruction efforts have successfully restored the tangible fabric of the area, they have simultaneously diminished its intangible heritage, including cultural memory and symbolic meaning. This study addresses that gap by identifying the constituent elements of sense of place that can inform the revitalisation of Gampong Pande’s identity as a post-disaster heritage site. The research employs a qualitative methodology, drawing on field observations, semi-structured interviews, and documentary analysis of planning instruments. The analytical framework integrates the triadic model of sense of place comprising form (physical setting), activity (social practices), and meaning (symbolic and cultural associations) with the evaluative dimensions of the Project for Public Spaces (1998). The findings reveal that Gampong Pande retains a rich constellation of historical, symbolic, and ecological assets. However, these assets remain underutilised due to fragmented management, insufficient interpretive infrastructure, the absence of designed public spaces to support community participation, and the lack of a coherent visual and spatial narrative. In response, the study proposes a set of multi-dimensional development principles grounded in place-based theory, encompassing spatial, socio-cultural, and symbolic dimensions. These principles are operationalised through context-sensitive design criteria and modular guidelines aimed at guiding future revitalisation initiatives. The study contributes to the academic discourse on heritage-based tourism planning and offers an applicable model for the sustainable redevelopment of disaster-impacted historic environments.